Pluralismo bajo control: evolución de la Ley de partidos políticos en Argelia - Pérez Beltrán, Carmelo (El Colegio de México, 2017)
This article studies the evolution of Algerian law on the creation and functioning of political parties from the country’s independence in 1962 up to the present time. We can distinguish between three periods that gave birth to the 1989 Law of Political Associations, the 1997 Organic Law of Political Parties, and the current 2012 Organic Law of Political Parties. This study takes as its point of departure a double hypothesis: that the law of political parties has followed an increasing repressive trend, and that it is a legal instrument serving the political and social strategies of the establishment in order to limit the field of action of the political opposition